2006
DOI: 10.1111/j.0022-1112.2006.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated antipredator conditioning: a pathway to habituation or to better avoidance?

Abstract: Hatchery-reared juveniles of Arctic charr Salvelinus alpinus were conditioned to the odours of Arctic charr-fed pikeperch Sander lucioperca in the absence of any other cues. Accordingly, there was no physical threat of capture for the Arctic charr. It was evident from the subsequent survival tests that a single exposure to predator odours was enough to increase Arctic charr survival compared to predator-naı¨ve control fish whist under direct threat from live predators. Instead of habituating to predator odours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 90 publications
2
63
2
Order By: Relevance
“…Knowledge of the specific effects of learning has formed the basis of programmes of 'life skills training' for cultured fish of various species. For example, predator-naive Arctic charr exposed to the odour of a piscivorous fish followed by an encounter with a predator become more responsive to the odour alone, especially if they have observed a trained conspecific respond to predator odour (Vilhunen et al 2005; Chapter 8).…”
Section: Mitigating the Effects Of Domestication And Captive Rearingmentioning
confidence: 99%
“…Knowledge of the specific effects of learning has formed the basis of programmes of 'life skills training' for cultured fish of various species. For example, predator-naive Arctic charr exposed to the odour of a piscivorous fish followed by an encounter with a predator become more responsive to the odour alone, especially if they have observed a trained conspecific respond to predator odour (Vilhunen et al 2005; Chapter 8).…”
Section: Mitigating the Effects Of Domestication And Captive Rearingmentioning
confidence: 99%
“…The question remains if repeated exposure over time results in enhanced learning opportunities in which the learned response is greater (stronger) than that resulting from a single conditioning event or if the retention is extended, or both. Vilhunen (2006) conditioned hatchery-reared Arctic charr juveniles to the odour of pikeperch (Sander lucioperca, Percidae) which had been fed a diet of Arctic charr once or four times (with 4 days between each conditioning). Vilhunen (2006) reports stronger antipredator responses (relative to unconditioned controls) by charr exposed four times to the predator.…”
Section: Retention: the Forgotten Component Of Learningmentioning
confidence: 99%
“…Vilhunen (2006) conditioned hatchery-reared Arctic charr juveniles to the odour of pikeperch (Sander lucioperca, Percidae) which had been fed a diet of Arctic charr once or four times (with 4 days between each conditioning). Vilhunen (2006) reports stronger antipredator responses (relative to unconditioned controls) by charr exposed four times to the predator. In addition, when exposed to a live predator during staged encounters, those that received multiple exposures had a higher probability of survival than did those conditioned a single time.…”
Section: Retention: the Forgotten Component Of Learningmentioning
confidence: 99%
“…These populations are fully maintained by reintroductions from hatchery stocks after hydroelectric schemes destroyed their primary spawning grounds. Initial studies revealed that socially acquired avoidance of predator odours is particularly effective means of training naïve fishes to recognise predators (Vilhunen et al 2005) and these early exposures to predators do lead to improved survival upon subsequent contact with live predators (Vilhunen 2006). …”
Section: Antipredator Behaviourmentioning
confidence: 99%